Clinical functional MRI of sensorimotor cortex using passive motor and sensory stimulation at 3 tesla - Blatow, Maria; Reinhardt, Julia; Riffel, Katharina; Nennig, Ernst; Wengenroth, Martina; Stippich, Christoph (Journal of magnetic resonance imaging, 2011)
Purpose: To establish a passive motor paradigm for clinical functional MRI (fMRI) that could be beneficial for patients with motor or attention deficits who are not able to perform active motor tasks. Materials and Methods: A novel standardized sensorimotor fMRI protocol was applied in 16 healthy volunteers at 3 Tesla (T) using active and passive motor tasks as well as sensory stimulation of hands and feet. Data analysis was carried out individually using a dynamic thresholding routine. Results: Active motor tasks yielded time efficient and robust blood-oxygen-level-dependent (BOLD) signals in primary motor cortex. Noteworthy, it was possible to achieve equal activation levels within identical anatomical localization for passive and active motor tasks with these paradigms. Conclusion: Patients unable to perform active movements can benefit from paradigms with passive motor and sensory stimulation. Therefore, we recommend these paradigms for functional somatotopic mapping of the central region at 3T in clinical routine. J. Magn. Reson. Imaging 2011;. © 2011 Wiley-Liss, Inc.
Gesehen am 30.03.2022